2020
DOI: 10.3389/fgene.2020.571274
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel SARS-CoV-2 Drug Targets by Host MicroRNAs and Transcription Factors Co-regulatory Interaction Network Analysis

Abstract: Understanding the host regulatory mechanisms opposing virus infection and virulence can provide actionable insights to identify novel therapeutics against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). We have used a network biology approach to elucidate the crucial factors involved in host responses involving host–microRNA (miRNA) interactions with host and virus genes using recently published experimentally verified protein–protein interaction data. We were able to identify 311 host genes to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 53 publications
2
52
0
Order By: Relevance
“…Sardar et al [180] applied a network biology approach to elucidate key factors involved in miRNA interactions with the host and viral genes. Based on the analysis of the gene regulatory network, it was found that the five major genes, HMOX1, DNMT1, PLAT, GDF1, and ITGB1, are involved in the induction of interferon IFN-α2b, epigenetic modification, and modulation of antiviral activity, making it possible to identify new targets for potential candidates for antiviral drugs.…”
Section: Preliminary In Silico Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Sardar et al [180] applied a network biology approach to elucidate key factors involved in miRNA interactions with the host and viral genes. Based on the analysis of the gene regulatory network, it was found that the five major genes, HMOX1, DNMT1, PLAT, GDF1, and ITGB1, are involved in the induction of interferon IFN-α2b, epigenetic modification, and modulation of antiviral activity, making it possible to identify new targets for potential candidates for antiviral drugs.…”
Section: Preliminary In Silico Studiesmentioning
confidence: 99%
“…Further analysis of miRNA expression selected 49 miRNAs expressed in the lung tissues. They have also identified 38 miRNAs targeting 143 host genes, whose expression is responsible for antiviral activity [180]. Interestingly, six antiviral miRNAs, miR-1-3p, miR-17-5p, miR-199a-3p, miR-429, miR-15a-5p, and miR-20a-5p, have been reported to play a role in respiratory diseases influenza A and respiratory syncytial virus.…”
Section: Preliminary In Silico Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Never before has a viral genome been sequenced so globally in such a short time. Even so, numerous reports revealed potential adaptations at the nucleotide (nt), amino acid (aa) and structural heterogeneity of viral proteins, particularly in the S protein (Sardar et al, 2020). At the moment, the world’s concern is focused in about four functionally well-defined variants, B.1.1.7 (Alpha), B.1.351 (Beta), P.1 (Gamma) and B.1.617.2 (Delta) associated with viral fitness changes (Faria et al, 2021; Hodcroft, 2021; McCallum et al, 2021; Tang et al, 2021; Tegally et al, 2021).…”
Section: Introductionmentioning
confidence: 99%